COVID-19 Pandemic in Malaysia: Managing Infodemic through Press Council: (Pandemik COVID-19 di Malaysia: Mengurus Infodemik melalui Majlis Akhbar) (Kanun: Jurnal Undang-undang Malaysia, 2021)
The online dissemination of fake news and disinformation phenomenon has become increasingly rampant as the world continues to face the COVID-19 pandemic. The overabundance of available information on a subject matter, known as infodemic, has negatively affected the effort to fight the pandemic. The phenomenon of infodemic has also amplified anxiety and mistrust among the people against the authorities' effort to curb the spread of COVID-19. Strict legal actions have been taken by the authorities in their crusade against the infodemic. Regardless, these actions have been construed by critics as being ineffective, draconian, and undemocratic. Thus, the main objective of this study is to re-evaluate the effectiveness of existing related laws in Malaysia that make it difficult to regulate infodemic. This study also proposes the establishment of a Press Council to curb misinformation and manage infodemic. To achieve the research objective, this study adopts a qualitative methodology in formulating its findings, which is mainly through textual analysis of legislations as well as semi-structured interviews.Keywords: Constitutional law, freedom of speech, freedom of press, media laws, Media Council, infodemic